Development of Nanoemulsion containing Piper betle Essential Oil as an effective natural insecticide - Mohamed Nasir, Nur Aliaa (2019)
The study aimed to prepare nanoemulsion containing Piper belle or betel leaf essential oil and to determine the effectiveness of the nanoinsectide on insects. The formulation of nanoemulsion was obtained from the points plotted on the ternary phase diagram for the system that consists of water, oil (soybean oil), surfactant (Tween 80) and co-surfactant (glycerol) of the previous research. The nanoemulsion containing Piper betle essential oil was formulated using 60% Tween 80 + glycerol, 30% water, and 10% oil which consist of Piper betle essential oil and soybean oil with ratio 8:2. The dark yellow color essential oil of Piper belle was obtained by steam distillation process. Nanoemulsion was formed by low energy method, which is spontaneous emulsification method. All the tests conducted to identify the validity of Piper belle essential oil and the final nanoemulsion showed positive results. The bioassay test conducted to test the effectiveness of nanoinsecticide also showed positive results, as it was able to cause the mortality of the houseflies (Musca domestica). This was due to the high concentration of Piper belle essential oil in the formulation of nanoinsecticide and the ability of the nanoemulsion to deliver the bioactive compound of Piper belle essential oil to the target site.